ANALISIS YURIDIS PASAL 27 PERPRES NO. 38 TAHUN 2015 DALAM PENGADAAN TANAH UNTUK PERENCANAAN PROYEK KPBU - Afifah, Nisa; Salsabilla Syafa’, Nadhifa; Nur Fazila, Arina; Abdul Kholik, Muhamad (SUPREMASI: Jurnal Pemikiran, Penelitian Ilmu-ilmu Sosial, Hukum dan Pengajarannya, 2025)
This study is entitled “Juridical Analysis of Article 27 of Presidential Regulation No. 38 of 2015 on Land Procurement for the Planning of Public Private Partnership (PPP) Projects.” The purpose of this research is to identify and analyze the juridical obstacles that arise in the implementation of Article 27 of Presidential Regulation No. 38 of 2015 concerning land procurement for Public Private Partnership (PPP) projects, as well as to understand and explain the legal framework of land procurement within the PPP scheme and the extent to which such regulation provides legal certainty for the parties involved. The method used is normative juridical research with statutory and conceptual approaches through qualitative–descriptive analysis of primary and secondary legal materials. The results show that the provisions of Article 27 play a strategic role in ensuring land availability and legal certainty for the implementation of PPP projects. However, its implementation still faces several obstacles, including overlapping regulations, procedural delays, limited budgets, compensation disputes, and weak inter-institutional coordination. Therefore, regulatory harmonization and institutional strengthening are required to ensure that Article 27 effectively guarantees a balance between legal certainty, justice, and expediency in PPP projects.